Lifelong prevention of cardiovascular disease. Part I: preconceptional, prenatal and infant periods of life - O. V. Kopylova; A. I. Ershova; A. N. Meshkov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
Current prophylactic actions prevent or significantly delay the majority of cardiovascular diseases (CVD). Various factors are interconnected and affect a person throughout his life, determining the risk of CVD. This indicates the need for preventive measures at all stages of life and even before birth. The beneficial effects of CVD prevention are realized through various genetic, epigenetic and metabolic mechanisms. Due to the fact that many risk factors for CVD have a cumulative effect, the introduction of preventive measures from the earliest life stages will be most effective. The purpose of the article is to consider various aspects of CVD prevention in the preconceptional, prenatal and infant periods.